FV 5. Stochastic resonance therapy induces increased movement related caudate nucleus activity. Issue 9 (September 2016) - Kaut, O.; Becker, B.; Schneider, C.; Fliessbach, K.; Hurlemann, R.; Wüllner, U.
Abstract : Objective: Whole body vibration means a supplementation of canonical physical treatment and is performed while probands stand on a vibrating platform. Therapeutic vibration can be generated as non-stochastic vibratory pattern, which is referred to as stochastic resonance (SRT). Despite the widespread use of SRT its neurophysiological mechanism is still unclear. Design: We performed a randomized sham-controlled double-blinded trial.The experimental group received 6 cycles of SRT with a frequency of 7 Hzusing the SR-Zeptor device, the sham group 1 Hz. At baseline 1, 5T fMRI was performed in resting state and finger/foot tapping test. A second fMRI was performed after SRT as sham treatment in both groups. Subsequently, a second cycle of SRT as sham or verum with consecutive fMRI was performed, followed by a final fMRI on day 2 (Fig. 1 ). Subjects: Nineteen healthy volunteers were allocated to the experimental or sham group, respectively. Results and conclusion: Subsequent analyses of specific effects revealed a significant treatment x time interaction effect ( t  = 4.10, p  < 0.05, SVC FWE-corrected) in the left caudate nucleus during intermediate difficulty comparing pre vs. post SRT treatment in the verum group (Fig. 2 ). This proof-of-concept study suggests the existence of cerebral effects of SRT.